A choice architect’s guide to the (autonomous) galaxy: a systematic scoping review of nudge intrusiveness in food choices - Dominic Lemken; Ainslee Erhard; Simone Wahnschafft (Humanities & Social Sciences Communications, 2024)
Abstract In seeking to uphold consumer autonomy in the design and implementation of nudge interventions, choice architects must concern themselves with preserving both the availability of options made to consumers (freedom of choice), and the capacity of consumers to deliberate and choose (agency) Several studies aim to examine the extent to which nudges truly uphold autonomy; however, most examine self-reported perceived intrusiveness on autonomy, rather than considering autonomy from the perspective of how nudges are designed. Leveraging a systematic scoping review of nudges related to food choice (N = 146), a common policy arena for nudge interventions, we develop a typology of three mechanisms of nudge design that, when not considered, could unduly intrude upon autonomy: (1) the effort to opt out, delineated along economic and physical sub-dimensions; (2) affective influence, such as social reference messaging and emotional appeals; and (3) non-transparency, including of the nudge itself and of non-nudged alternative options. We discuss how each mechanism manifested in reviewed studies, and ultimately offer possible criteria that can be used to evaluate nudge intrusiveness along each mechanism. This typology can support choice architects to discern how nudges might better protect consumer autonomy, and ultimately uphold it in pursuit of behavior change. Our scoping review further provides empirical support for the concept of resistible yet effective nudges.